Mobile Robot Dengan Pengontrolan Perintah Suara Berbasis Android - Eko Sulistyo (Manutech : Jurnal Teknologi Manufaktur, 2017)
Control of mobile robot manually using remote control connected with cable has constraints that limited space of robot movement. For that developed mobile robot control system using bluetooth communication. The purpose of this research is to create a mobile robot control system through wireless communication using voice command instruction via application on Android using microcontroller type Arduino Mega2560. The methodology in this research is the voice instruction will be recorded by the application on Android, then matched with the database and then converted into characters in the form of strings and sent via bluetooth transmitter on Android to bluetooth receiver on mobile robot to be executed by program made on microcontroller robot. The results obtained include mobile robot can move to follow voice command instruction that is given include command forward, backward, turn left and right only for one movement while in test result got error of movement equal to 1.55% with response time 4-7 second because the process of recording and translation of voice instructions on Android and also influenced by noise or other sounds that are not desired.